O processo de definição e implementação de objetivos numa organização publica do setor saude : do conjunto sanatorial de Curicica ao Hospital de Clinicas Basicas Raphael de Paula Souza - Lima, Sheyla Maria Lemos (1994)
The object of this dissertation is the process of definition and implementation of the objectives in a public health organization. A literature review of the theory of organization was made in order to identify how in different theoretical perspectives (rational, natural, political, and of integration) the objectives and the process of their definition and implementation in organizations are understood. Also, some characteristics of the organization were identified, those that can intefere in the above process due to the fact that they are public and need qualified staff for their operation. Based on these theoretical references a case study in a public health organization(Hospital Raphael de Paula Souza) was carried out on the process of transformation of its profile(from a hospital specialized in phthisiology to a general hospital) . Finaly, an adequate comprehension of complexity concerning the process of definition and implementation of the objectives in a public health organization, may contribute so that its managers can actively intefere in that process, and minimize the indefinition, incongruity and irresponsability of its objectives. A reversion in this situation wiU also contribute so that in this organization efficiency and efficacy may be reached in order to attend public needs, the main reason for its existence.